Dwarfing-canopy and rootstock cultivars for fruit trees - Donadio, Luiz Carlos [UNESP]; Lederman, Ildo Eliezer; Roberto, Sergio Ruffo; Stucchi, Eduardo Sanches (FapUNIFESP (SciELO), 2019)
As fruit trees generally have a large size, the production of small or even dwarf trees is of great interest for most of fruit crops. In this review, some of the main tropical, subtropical and temperate fruit trees that have small or even dwarfing cultivars are approached. The causes of dwarfism, although the use of dwarfing rootstocks, is the main theme of this review. The factors that affect the size of the fruit trees are also approached, as well the dwarf cultivars of banana, papaya and cashew, and the dwarf rootstocks for guava, mango, anonaceae, loquat, citrus, apple and peach trees.
Cultivares-copa e porta-enxertos ananicantes para plantas frutíferas
Keywords: Dwarf fruit trees; High-density plantings; Spacings